Eye movement corpora in Adyghe and Russian: an eye-tracking study of sentence reading in bilinguals - Zdorova, Nina; Parshina, Olga; Ogly, Bela; Bagirokova, Irina; Krasikova, Ekaterina; Ziubanova, Anastasiia; Unarokova, Shamset; Makerova, Susanna; Dragoy, Olga (Frontiers in Psychology, 2023)
The present study expands the eye-tracking-while reading research towards less studied languages of different typological classes (polysynthetic Adyghe vs. synthetic Russian) that use a Cyrillic script. In the corpus reading data from the two languages, we confirmed the widely studied effects of word frequency and word length on eye movements in Adyghe-Russian bilingual individuals for both languages. We also confirmed morphological effects in Adyghe reading (part-of-speech class and the number of lexical affixes) that were previously shown in some morphologically-rich languages. Importantly, we demonstrated that bilinguals' reading in Adyghe does differ quantitatively (the effect of language on reading times) and qualitatively (different effects of landing and previous/upcoming words on the eye movements within a current word) from their reading in Russian.